2019
DOI: 10.1177/1533033819892264
|View full text |Cite
|
Sign up to set email alerts
|

MiR-142-5p Acts as a Significant Regulator Through Promoting Proliferation, Invasion, and Migration in Breast Cancer Modulated by Targeting SORBS1

Abstract: Background: Numerous researches have demonstrated that miR-142-5p plays significant roles in several cancers, although the functional characteristic of miR-142-5p in breast cancer has not been determined. This study is designed to explore the biological significance of miR-142-5p in breast cancer clinical implication and mechanism of action. Methods: The differential expression patterns of miR-142-5p and Sorbin and SH3 domain-containing protein 1 and correlations between them and clinical significances were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 26 publications
(27 reference statements)
1
18
0
Order By: Relevance
“…Previous studies had reported that miR-142-5p repressed the advancement of gastric cancer, breast cancer, and cervical cancer by, respectively, targeting CYR61, SORBS1, and PIK3AP1. [22][23][24] However, miR-142-5p played a carcinogenic role in renal cell cancer and colorectal cancer. 25,26 In addition, miR-142-5p exerted a tumorrepressive role in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had reported that miR-142-5p repressed the advancement of gastric cancer, breast cancer, and cervical cancer by, respectively, targeting CYR61, SORBS1, and PIK3AP1. [22][23][24] However, miR-142-5p played a carcinogenic role in renal cell cancer and colorectal cancer. 25,26 In addition, miR-142-5p exerted a tumorrepressive role in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…By analysing the GO functions of these 11 DEGs, we found that ITGA7 , ITGBL1 and SORBS1 were mainly involved in cell adhesion ( Table 3 ). We observed that ITGA7 had a direct interaction with ITGBL1 in PPI network ( Figure 3 ), which suggested that they might be coexpressed, and all three genes were upregulated DEGs that regulated cell proliferation, invasion and migration in cancers [ 47–51 ]. It is of great significance to analyse their survival in obstetrics- and gynaecology-related tumours ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it promoted epithelial-to-mesenchymal transition (EMT) of colorectal cancer (CRC) cells [ 55 ] and had the same characteristics in ovarian cancer [ 51 ] and prostate cancer [ 50 ]. SORBS1 overexpression promoted CRC growth and migration via inhibition of AHNAK expression [ 56 ], while SORBS1 was downregulated in breast cancer and led to poor prognosis [ 47 ]. Silencing of SORBS1 promoted the EMT process and attenuated chemical drug sensitivity, and it is a potential inhibitor of metastasis in cancer [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…29 Yu et al demonstrated that miR-142-5p promotes proliferation, invasion, and migration of breast cancer by targeting SORBS1. 45 Song et al revealed that SORBS1 silencing increases the migration and invasion of breast cancer cells by activating JNK/cJun and promotes EMT. The chemosensitivity was reduced by inhibiting p53.…”
Section: Discussionmentioning
confidence: 99%